Power and emission estimation of plastic waste pyrolysis-derived fuel blends in internal combustion engines - Hadi Susilo, Sugeng; Mashudi, Imam; Santoso, Santoso; Hardjito, Agus; Pebrianti, Dwi (Technology Center PC®, 2024)
Energy, especially from fossil fuels, is essential for everyday life, while plastic waste is an increasing envi-ronmental threat. Plastic waste disposal methods such as landfilling and burning cause pollution. Therefore, a process is needed that converts plastic waste into fuel. The object of the study is the engine performance. The problem to be solved is the relationship between the use of a mixture of fossil fuels and pyrolysis fuel on the per-formance of internal combustion engines.This research uses a systematic data collection pro-cess to obtain accurate and reliable results. The nec-essary equipment, including a dynamometer and gas analyzer, was prepared, and the engine was warmed up to a stable operating temperature of 80°C. The motor-bike is then positioned on the dynamometer with the rear tires aligned and the front tires secured to pre-vent movement. Data collection was carried out at engine speeds of 2000, 3000, 4000, 5000, and 6000rpm, using three fuel mixtures: 10% plastic pyrolysis fuel with 90% RON 90, 20% plastic pyrolysis fuel with 80% 90 RON, and 30% plastic pyrolysis fuel with 70%RON90. Each test was repeated three times, with the output power measured using a dynamometer and exhaust emissions (CO and HC levels) recorded using a gas analyzer. The test results show that the opti-mal fuel mixture to produce maximum engine power is a PE-RON 90 mixture with a ratio of 20:80, pro-viding the best performance at medium to high engine speeds(3000–6000rpm) with low CO emissions. The highest power output (1.05) occurs at 4000rpm, while the PE-RON 90 30:70 alloy produces the best power performance at 6000rpm (0.78% CO). Additionally, the pyrolysis fuel blend significantly reduces CO and HC emissions, with the PE-RON 90 30:70 blend show-ing the lowest CO (0.78% at 6000rpm) and consistent-ly reducing HC emissions across therpm rangeKeywords: plastic waste, pyrolysis, fuel mixture, power, exhaust gas, types of plastic